2013
DOI: 10.1248/bpb.b12-00479
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Shichimotsu-koka-To on Irreversible Thy-1 Nephritis

Abstract: Oxidative stress and peritubular capillary (PTC) injury are involved in the progression of chronic kidney disease (CKD). We investigated protective effects of Shichimotsu-koka-To (SKT), a Japanese traditional Kampo prescription, against nephrosclerosis and hypertension on a CKD model due to irreversible nephritis. Six-week-old male Wistar rats were subjected to uninephrectomy, and to injection of rabbit anti-thymocyte serum. SKT treatment was continued for 15 weeks, blood pressure was measured, and then renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The effectiveness of shichimotsukokato in this case may be due to the amelioration of potential kekkyo . In addition to this, it has been reported that shichimotsukokato has a protective effect against renal dysfunction associated with hypertension and nephritis [8,9]. In this case, the patient had severe renal dysfunction associated with ANCA‐associated nephritis and hypertension.…”
Section: Discussionmentioning
confidence: 70%
“…The effectiveness of shichimotsukokato in this case may be due to the amelioration of potential kekkyo . In addition to this, it has been reported that shichimotsukokato has a protective effect against renal dysfunction associated with hypertension and nephritis [8,9]. In this case, the patient had severe renal dysfunction associated with ANCA‐associated nephritis and hypertension.…”
Section: Discussionmentioning
confidence: 70%